2020
DOI: 10.1093/eep/dvaa010
|View full text |Cite
|
Sign up to set email alerts
|

TCDD-induced multi- and transgenerational changes in the methylome of male zebrafish gonads

Abstract: The legacy endocrine disrupting chemical and aryl hydrocarbon receptor agonist, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), is produced as a byproduct of industrial processes and causes adverse health effects ranging from skin irritation to cancer. TCDD endpoints are also observed in subsequent, unexposed generations; however, the mechanisms of these multi- and transgenerational effects are unknown. We hypothesized an epigenetic mechanism, specifically DNA methylation for the transgenerational, male-mediated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…In permethrin exposure, changes of DMR in both sexes on chromatin remodeling 24 (chr24) and vimentin (vim) genes were observed, with modifications in the same sites from F0 to F2; furthermore, sex-specific differentially methylated regions (DMR) were found related to the paternal inheritance of F0 to F2 in fragile-X mental retardation protein translational regulator 1 (fmr1) and prepronociceptin b (pnocb) genes, both related to the development of the zebrafish nervous system (Blanc et al, 2021). As with permethrin, Akemann et al (2020) observed that exposure to 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) in male zebrafish did not generate changes in global methylation in gonads at any generation; however, they did observe DMRs from F0 to F2. In the F1 generation, 159 genes with differential methylation and expression were identified, while in F2 there were five, pre-B-cell leukemia homeobox 3b (pbx3b; transcriptional activator), si:dkey-266f7.5 (unknown function), snail family zinc finger 3 (snai3; roles in mesodermal formation during embryogenesis; involved in spermatogenesis), transmembrane protein 132E (tmem132e; required for normal inner ear hair cell function and hearing), and calpain 7 (capn7; member of the calpain family of proteins), all except tmem132e showed differential methylation in the three generations.…”
Section: Dna Methylation In Zebrafishmentioning
confidence: 99%
“…In permethrin exposure, changes of DMR in both sexes on chromatin remodeling 24 (chr24) and vimentin (vim) genes were observed, with modifications in the same sites from F0 to F2; furthermore, sex-specific differentially methylated regions (DMR) were found related to the paternal inheritance of F0 to F2 in fragile-X mental retardation protein translational regulator 1 (fmr1) and prepronociceptin b (pnocb) genes, both related to the development of the zebrafish nervous system (Blanc et al, 2021). As with permethrin, Akemann et al (2020) observed that exposure to 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) in male zebrafish did not generate changes in global methylation in gonads at any generation; however, they did observe DMRs from F0 to F2. In the F1 generation, 159 genes with differential methylation and expression were identified, while in F2 there were five, pre-B-cell leukemia homeobox 3b (pbx3b; transcriptional activator), si:dkey-266f7.5 (unknown function), snail family zinc finger 3 (snai3; roles in mesodermal formation during embryogenesis; involved in spermatogenesis), transmembrane protein 132E (tmem132e; required for normal inner ear hair cell function and hearing), and calpain 7 (capn7; member of the calpain family of proteins), all except tmem132e showed differential methylation in the three generations.…”
Section: Dna Methylation In Zebrafishmentioning
confidence: 99%
“…For example, in nematodes, the plastic component Bisphenol A causes transgenerational reproductive defects that are dependent on two histone modifications, H3K9me3 and H3K27me3 (Camacho et al, 2018; Weinhouse et al, 2018). Endocrine disruptors also lead to detectable transgenerational changes in DNA methylation in Zebrafish (Akemann et al, 2020) as well as in rats (Gillette et al, 2018). In the latter study, the authors examined the number of differentially methylated regions (DMRs) occurring in sperm and specific brain nuclei involved in stress response and social behavior caused by in utero exposure to two endocrine disruptors Vinclozolin and the polychlorinated biphenyl mixture A1221.…”
Section: The Inheritance Of Acquired Characteristics and The Return Of Soft Inheritancementioning
confidence: 99%